Experimental and Numerical Study of the Failure Behavior of Intermittent Rock Joints Subjected to Direct Shear Load - Xiang Fan; Kaihui Li; Hongpeng Lai; Qihua Zhao; Zhenhua Sun (Advances in Civil Engineering)
Two series of intermittent rock joints containing three joints arranged along the central shear axis were considered in this study. The failure behavior under direct shear loads was investigated by means of both physical tests and numerical simulations. The cracking behavior was found to be distinctly associated with the joint arrangement. Several types of main and secondary cracks were identified. The variation trends of the crack initiation stress ratio with inclination angle were analyzed and found to be partly different for the two series of intermittent joints. The whole fracturing process was characterized by three phases. Not all samples have to experience all three phases. The second phase is alternative and can be reflected by the shearing curve. Hence, two types of shearing curves, including single and double peaks, were identified. The double peak is due to the extrusion or sawteeth cutting in the second phase. Moreover, the numerical micromechanical analysis was performed to explain the shear behavior using the contact force and microcrack within the specimen. Based on the numerically measured local stresses, maximum and minimum principal stresses around the middle joint at crack initiation stress and peak shear stress were analyzed.